Striving for a thorough understanding of the discipline: A commentary on the first four papers - Entwistle, Noel (Psychology: the Journal of the Hellenic Psychological Society, 2020)
This commentary looks at the first four articles, those by Hazel Francis, David Hay, Max Scheja and Anna Bonnevier, and Lennart Svensson. Each of these four papers examines the processes by which students come to understand, or fail to understand, ideas within academic disciplines. It concentrates on those ideas introduced in the four papers that contribute most strongly to the main theme of this Special Issue in clarifying the nature of the learning processes through which students strive to reach a thorough understanding. Although the theoretical frameworks used in the analyses are quite different, the conclusions reached nevertheless seem to offer complementary views of how students come to understand. In this commentary, certain aspects from each of the articles are highlighted, leading to a more general discussion to consider how these papers extend the research on student understanding.